Fructose -induced maternal metabolic syndrome leads to cerebral oxidative stress, neuroinflammation and neurobehavioral impairments in offspring - Prado Spalm, Facundo Heber (2022)
Since fructose (F) consumption has been linked to the aetiology of metabolic syndrome (MetS), we studied the implications of long- term effects of F consumption by dams on rat offspring neurode- velopment and neurobehavior. Two-month-old Wistar rats were fed standard chow and drank water (control, C) or 20% F (ad libitum) for 10 weeks before mating and throughout pregnancy and lactation. In dams, macronutrient and caloric intake were calculated and blood samples were collected for biochemical analysis. At postnatal day 1 (PN1) oxidative and inflammatory brain status were evaluated in male (♂) and female (♀) pups. The remaining litters (reduced to 8 pups with equal sex ratios) were reassigned to a nursing dam from the C group (NC) or from the F group (NF). Offspring were evaluat- ed for sensorimotor reflexes, reciprocal social interaction, memory retention, novel object recognition and nociception. A p value <0.05 was regarded as statistically significant. F consumption in dams in- duced MetS, increased caloric and carbohydrate intake and reduced protein and fat consumption. Weight, waist circumference and fat % were also higher in F dams. At PN1, ♀ from the F group showed enhanced lipid peroxidation (TBARS) levels, elevated catalase ac- tivity and increased superoxide dismutase protein expression in the whole brain. Neuroinflammation was corroborated by increased pro- tein expression of cyclooxygenase 2. The acquisition of developing milestones was delayed in ♀ from F-NC and F-NF groups. In com- parison with C-NC litter, aggressive social behavior increased while memory retention and nociception were reduced in offspring from F-NC. The ability of recognizing a previously presented stimulus was affected only in ♂ from the F-NC group. These findings suggest that F-induced maternal MetS results in offspring neurodevelopmen- tal delay and neurobehavioral changes probably associated with early brain oxidative stress and inflammation. Interestingly, offspring gender differences were noted